Methods of making the right decision Manager at Air Traffic Service - Харченко, В.П.; Буцик, І.М.; Алєксєєв, О.М. (Proceedings of National Aviation University (archive), 2009)
In the article certain and the considered basic methods in the system “air traffic controller − environment − crew", which determine the decision-making by air traffic control.